Neuraxial analgesia is not associated with an increased risk of post-partum relapses in MS. (April 2019) - Lavie, Caroline; Rollot, Fabien; Durand-Dubief, Françoise; Marignier, Romain; Ionescu, Iuliana; Casey, Romain; Moreau, Thibault; Tourniaire, Patricia; Hutchinson, Michael; D'Hooghe, Marie Béatrice; Laplaud, David-Axel; Clavelou, Pierre; et al.
Background: Obstetrical analgesia remains a matter of controversy because of the fear of neurotoxicity of local anesthetics on demyelinated fibers or their potential relationship with subsequent relapses. Objective: To assess the impact of neuraxial analgesia on the risk of relapse during the first 3 months post-partum, with a focus on women who experienced relapses during pregnancy. Methods: We analyzed data of women followed-up prospectively during their pregnancies and at least 3 months post-partum, collected in the Pregnancy in Multiple Sclerosis (PRIMS) and Prevention of Post-Partum Relapses with Progestin and Estradiol in Multiple Sclerosis (POPARTMUS) studies between 1992–1995 and 2005–2012, respectively. The association of neuraxial analgesia with the occurrence of a post-partum relapse was estimated by logistic regression analysis. Results: A total of 389 women were included, 215 from PRIMS and 174 from POPARTMUS. In total, 156 women (40%) had neuraxial analgesia. Overall, 24% experienced a relapse during pregnancy and 25% in the 3 months post-partum. Women with a pregnancy relapse were more likely to have a post-partum relapse (odds ratio (OR) = 1.83, p  = 0.02), independently of the use of neuraxial analgesia. There was no association between neuraxial analgesia and post-partum relapse (OR = 1.08, p  = 0.78). Conclusion: Neuraxial analgesia was not associated with an increased risk of post-partum relapses, whatever multiple sclerosis (MS) activity during pregnancy.